2019
DOI: 10.3390/rs11101196
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Assessment of Multi-Source Satellite Soil Moisture Products and Reanalysis Data for the Tibetan Plateau

Abstract: Soil moisture is a key variable in the process of land–atmosphere energy and water exchange. Currently, there are a large number of operational satellite-derived soil moisture products and reanalysis soil moisture products available. However, due to the lack of in situ soil moisture measurements over the Tibetan Plateau (TP), their accuracy and applicability are unclear. Based on the in situ measurements of the soil moisture observing networks established at Maqu, Naqu, Ali, and Shiquanhe (Sq) by the Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…The analysis showed that all three of them had an inverse relationship, with the highest agreement found in the ERA5 product (R: −0.93). A recent study which assessed satellite and reanalysis products over the Tibetan Plateau region of China also reported the reliability of ERA5 soil moisture product [42], confirming the results obtained in this study. The colors of the plots in Figure 6 correspond to NDVI densities.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis showed that all three of them had an inverse relationship, with the highest agreement found in the ERA5 product (R: −0.93). A recent study which assessed satellite and reanalysis products over the Tibetan Plateau region of China also reported the reliability of ERA5 soil moisture product [42], confirming the results obtained in this study. The colors of the plots in Figure 6 correspond to NDVI densities.…”
Section: Discussionsupporting
confidence: 90%
“…Results of analysis and validation of existing CDR/ECV data (e.g., those from ESA CCI) [37] A set of new and consistent land surface variables for the TPE (LST, soil moisture, soil thermal and hydraulic properties) Integration of these new consistent dataset into research of WP2 (see results under WP2) Development of observation operators for assimilation of microwave observation from SMOS and SMAP into the modelling system Analysis of monsoon dynamics in relation to changes of plateau surface characteristics [38] PhD theses…”
Section: Wp Resultsmentioning
confidence: 99%
“…More cases under a weak synoptic background and high-resolution simulations are needed in the future to obtain a robust physical mechanism to enhance the capacity of the model ulteriorly. Previous studies have pointed out that the relationship of SMP is largely depended on the data source of the soil moisture [49,50], so more precise data with high spatial-temporal resolution, such as SMOS (Soil Moisture and Ocean Salinity), GLDAS (Global Land Data Assimilation Systems), and ERA5 (European Centre for Medium-Range Weather Forecasts Reanalysis 5) [51,52], is necessary to improve the model initial conditions. Besides, the climatic effects owing to the vegetation changes resulting from the Grain for Green Program (GFGP) over the Loess Plateau have received huge attention in recent years [30], while few studies have explored its impact on precipitation on convective scales [53].…”
Section: Conclusion and Discussionmentioning
confidence: 99%